Research Progress of Groundwater and Surface Water Interaction in Riparian Zone Based on Bibliometrics - Zhao, Yawei; Yang, Chen; Xie, Sijia (International Journal of Natural Resources and Environmental Studies, 2025)
The interaction between groundwater and surface water was a key link in the study of hydrological and ecological processes in riparian zones. Based on the literature of the SCI-E database of the core collection of Web of Science as the data source, the CiteSpace bibliometric tool was used to visualize the research literature on the interaction between groundwater and surface water in the riparian zone from the aspects of annual publication volume, research strength, subject distribution, and research hotspot frontier. The results showed that the number of research papers on the interaction between groundwater and surface water in the riparian zone was on the rise. The United States had the strongest research strength, while China needed to strengthen exchanges and cooperation with scientific research institutions in other countries. Research institutions such as the Chinese Academy of Sciences, Colorado State University, and the US Geological Survey had published a large number of papers. Soulsby C, Groffman P M, and Hill A R were the core authors. Journals such as Journal of Hydrology, Hydrological Processes, and Water Resources Research were the main carriers. Keyword co-occurrence analysis showed that the multi-level environmental interface dynamic process of surface water and groundwater, the coupling of hydrological-biogeochemical processes in riparian zones, and the eco-environmental effects of the interaction between groundwater and surface water were the core contents of the research on the interaction between groundwater and surface water in riparian zones. From keyword clustering and burst analysis, it could be seen that diversified comprehensive research methods, the source-sink model of nutrient elements in the riparian zone, the formation and evolution mechanism of groundwater under changing environments, and its geological-ecological effects were the frontier hotspots in the field of interaction between groundwater and surface water in the riparian zone.